Difference between revisions of "Equation 2.11 is not equal to the preceding expression from which it came"

From FBSwiki
Jump to: navigation, search
 
Line 8: Line 8:
 
|Page number=2-7
 
|Page number=2-7
 
|Line number=9
 
|Line number=9
|Current status=Pending
+
|Current status=Closed
 
}}
 
}}
 
Is (2.11) referring to the equation directly above it? [ g1/(g1+g2) == g1/(1+g1*g2)? ]
 
Is (2.11) referring to the equation directly above it? [ g1/(g1+g2) == g1/(1+g1*g2)? ]

Latest revision as of 12:01, 5 September 2019

Edition Second
Version number 3.0h
Submission date 4 Oct 2016
Your name Kai Kirk
E-mail address mailto:kkirk@caltech.edu
Chapter 2
Page number 2-7
Line number 9
Current status Closed

Is (2.11) referring to the equation directly above it? [ g1/(g1+g2) == g1/(1+g1*g2)? ]